The effects of the social status of the elderly in Libya on the way they institutionally interact and communicate with younger physicians - Wei, Li; Mayouf, Mayouf Ali (Journal of pragmatics, 2009)
This research investigates how elderly patients in Libya interact and communicate institutionally with younger physicians. In communities such as that in Sebha, Libya (Bedouin, Arab and Muslim) elderly people have important social status and power. Naturally occurring conversations between three elderly patients and their younger physicians were tape-recorded separately. The subjects were also interviewed. Conversation Analysis combined with social constructionist theories was employed as a method of data analysis. The analysis of the interviews shows that elderly patients and their younger physicians (subjects) perceive each other socially rather than institutionally. Younger physicians insist that they cannot practice their institutional concessions when the patients are elderly. They cannot produce interruption, overlap or verbal refusal. In comparison, elderly subjects suggest that they perceive their younger physicians like their younger sons. The analysis of the naturally occurring conversations reveals that elderly patients and younger physicians call each other as social actors (son/hajj or uncle) rather than institutional ones (doctor/sir). Elderly patients and younger physicians could not raise sexual topics or directly name sexual organs (e.g. rectum) related to the elderly patient's case. Moreover, elderly patients address their younger physicians with proverbs and religious expressions when describing their cases. The conversations’ exchange of turns was not thoroughly task-oriented. Rather, elderly patients address their younger physicians with social conversations (e.g. where are you from? Who is your cousin? Where do you live?). Elderly patient interactants manipulated the conversations’ time-span. Furthermore, they employed the least preferable repair strategy. This research concludes that elderly patients in Libya interact and communicate with their younger physicians in accordance to their social construction which shows prevalence over the institutional hierarchy of the interactants.